Magma and Mineral Composition Response to Increasing Slab-Derived Fluid Flux: Nevado de Longaví Volcano, Southern Chilean Andes - Sellés, Daniel; Dungan, Michael; Langmuir, Charles; Rodríguez, Ana Carolina; Leeman, William P. (Frontiers in Earth Science, 2022)
Nevado de Longaví volcano (NLV), in the Southern-Central Chilean Andes, has erupted during the Holocene magmas with compositions that are, in several ways, atypical for the region. These characteristics include elevated La/Yb ratios, in an area of only moderately thick crust, coupled with low concentrations of incompatible elements and elevated ratios of fluid-mobile to fluid-immobile elements, in addition to a mafic mineralogy dominated by amphibole. The petrology of the Holocene products of NLV have been related to the influence of an oceanic transform fault (Mocha Fracture Zone; MFZ) that supplies the mantle wedge with unusually high amounts of fluids via dehydration of serpentinite bodies hosted by the subducted oceanic lithosphere. Because the trace of this transform fault is oblique to the convergence vector, its position along the arc has varied through time, as has the magnitude of its influence on the nature of the magmas erupted at NLV. In this contribution we present the whole-rock and mineral chemistry of volcanic products from NLV, tied to a simplified stratigraphy, in order to document the secular changes experimented in the magmatic system as the oceanic fault approached its current position.